Effect Quality Of Health Insurance Service On Public Satisfaction Of Public Surgical Interior Ulin Hospital Banjarmasin - Mohdari Mohdari; R Topan Aditya Rahman; Muhammad Anshari Ridha (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2018)
Background: Health is a prosperous state of body, soul, and social that is possible every individual to live productively in a social and economical way. With this health, every individual can carry out activities as a living creature created by God Almighty so as to live productively both socially and economically. In regulating health problems, a special body is responsible for the maintenance of health assurance, where the agency must provide good service quality in order to achieve service satisfactionObjective: To know the Influence of Quality of health insurance Service to Patient Satisfaction in General Surgery Room Ulin Hospital BanjarmasinMethod: This research uses Analytical Survey approach using Cross-Sectional design method. With the number of samples of 58 respondents who use the health insurance service in the General Surgery Room Ulin Hospital BanjarmasinResult: From the statistical test result using Chi-Square obtained P-value of 0.000. this indicates that the value is smaller than Î± is â‰¤ 0.05 where in this case p â‰¤ Î± then the hypothesis Ha in a receipt which means there is a significant influence between the quality of health insurance service on patient satisfaction in the room General Surgery Ulin Hospital BanjarmasinConclusion: There is a significant influence on the quality of health insurance service on patient satisfaction in the room General Surgery Ulin Banjarmasin HospitalKeywords: Health Insurance Service (HIS), Quality, Hospital.